CELEBRITIES’ BODIES IN ACHIEVEMENT CULTURE: A STUDY OF JOURNALISTIC APPROACHES TO AMY WINEHOUSE - Brigida, Marcela Santos (Inventário, 2019)
Amy Winehouse (1983-2011) was an artist whose musical talent led her to the spotlight at an early age. Nevertheless, an elevated amount of media scrutiny focused on her body, physical appearance and personal life helped define the way in which the public viewed her. In this paper, I engage in an analysis of headlines and articles published about the singer in British broadsheets, tabloids and magazines to discuss how the press acted in the sense of turning Winehouse into a valuable, easily sellable commodity. As I analyse a selection of media pieces that focus on the artist’s physical appearance (as opposed to her musical career), I also seek to establish the point that the discourse pervasive to those pieces is heavily gendered, with Winehouse often being criticised for deviating from acceptable patterns of femininity. The discussion I propose here is supported by studies developed by researchers of Fame Studies such as Mike Featherstone (2010) and by Guy Debord’s seminal book Society of the Spectacle (1962). Under this light, Winehouse stands as an example how the press and social media deal with and approach celebrities in the age of what Byung-Chul Han has called the achievement society [Leistungsgesellschaft]. To the Korean philosopher, we have collectively moved past Foucault’s disciplinary world towards a model where the pressure to achieve is what moves and defines us. Considering that many celebrities are perceived as overachievers, this paper discusses the toll such pressure takes on a person when undertaken publicly, with society assessing their body and behaviour to the minutest detail, fundamentally establishing patterns of scrutiny that were not possible before the digital age.